2021
DOI: 10.3758/s13423-021-02012-w
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relations between spatial skills and mathematical performance: A meta-analysis

Abstract: Much recent research has focused on the relation between spatial skills and mathematical skills, which has resulted in widely reported links between these two skill sets. However, the magnitude of this relation is unclear. Furthermore, it is of interest whether this relation differs in size based on key demographic variables, such as gender and grade-level, and the extent to which this relation can be accounted for by shared domain-general reasoning skills across the two domains. Here we present the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 139 publications
(146 reference statements)
6
51
0
Order By: Relevance
“…This work has revealed that the association between phonological processing and mathematics holds when non-verbal IQ, executive functions and vocabulary are controlled for [10]. A similar pattern holds for the association between spatial ability and mathematics, which remains when fluid intelligence and verbal skill are controlled for [13]. In all, this suggests that the reported associations between a particular correlate and mathematics remain after some control for other domain-general cognitive factors.…”
Section: The Overall Pattern Of Associations and Their Moderating Var...mentioning
confidence: 58%
See 1 more Smart Citation
“…This work has revealed that the association between phonological processing and mathematics holds when non-verbal IQ, executive functions and vocabulary are controlled for [10]. A similar pattern holds for the association between spatial ability and mathematics, which remains when fluid intelligence and verbal skill are controlled for [13]. In all, this suggests that the reported associations between a particular correlate and mathematics remain after some control for other domain-general cognitive factors.…”
Section: The Overall Pattern Of Associations and Their Moderating Var...mentioning
confidence: 58%
“…Domaingeneral (or non-mathematical) factors are variables that are important for learning more broadly and that subserve various academic outcomes, that is they are not specific for learning in a particular domain, for which reason they are considered to be more general. These domain-general variables include executive functions [8] and working memory [9], phonological processing [10] and rapid automatized naming (RAN) [11], language [12], spatial ability [13,14], and fluid intelligence [15]. This apparently simple classification of domain-specific and domain-general factors is much more complicated than it seems, because it is not always clear what specific and general refer to and what is considered to be a domain.…”
Section: Correlates Of Individual Differences In Mathematical Cognitionmentioning
confidence: 99%
“…This sensory ability develops as children visually estimate objects’ width, height, and volume. Children’s ability to assess objects’ quality is associated with mathematical learning ( Atit et al, 2021 ). The participants also had volume sense and physical sense training in their second-grade mathematics curriculum ( Research Group of National Mathematics Curriculum Standards for Compulsory Education, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used structural equation modeling (SEM) to assess the relation between spatial abilities that are common across these measures and assessed the potential relation between distinct spatial measures and performance on word problems. Atit et al's (2022) meta-analyses, as mentioned, indicated that the strength of the relation between spatial and mathematical abilities is reduced with control of verbal and reasoning abilities. Studies of performance on word problems are consistent with these general trends, that is, intelligence and spatial abilities are concurrently predictive of this performance (Geary et al, 2000;Johnson, 1984;Kyttälä & Lehto, 2008).…”
Section: Spatial Abilities and Mathematicsmentioning
confidence: 93%